2018
DOI: 10.1007/s00264-018-4232-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimension-printed custom-made prosthetic reconstructions: from revision surgery to oncologic reconstructions

Abstract: Background The use of custom-made 3D-printed prostheses for reconstruction of severe bone defects in selected cases is increasing. The aims of this study were to evaluate (1) the feasibility of surgical reconstruction with these prostheses in oncologic and non-oncologic settings and (2) the functional results, complications, and outcomes at short-term follow-up. Methods We analyzed 13 prospectively collected patients treated between June 2016 and January 2018. Diagnoses were primary bone tumour (7 patients), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 45 publications
0
83
0
1
Order By: Relevance
“…Robotic systems have assisted with planning closed fracture reduction and reconstruction and in performing surgery remotely such as in telemedicine in small towns, rural areas, and war zones [3,12]. Oncologic reconstruction using robotic made implants is already performed with good results [13].…”
Section: The Clinical Applicationsmentioning
confidence: 99%
“…Robotic systems have assisted with planning closed fracture reduction and reconstruction and in performing surgery remotely such as in telemedicine in small towns, rural areas, and war zones [3,12]. Oncologic reconstruction using robotic made implants is already performed with good results [13].…”
Section: The Clinical Applicationsmentioning
confidence: 99%
“…When the failure of hip arthroplasty causes big acetabular defects, custom-made components promise good solutions with low complication rate [15]. Also, 3D-printed custom-made prostheses represent a promising reconstructive technique, both in musculoskeletal oncology and in challenging revision [16].…”
Section: Hipmentioning
confidence: 99%
“…In recent decades, with the development of technology, 3D-printing technology was reported that had enhanced the accuracy and individuation of orthopedic surgeries [7][8][9]. The use of 3D-printing technology in orthopedic surgery allows greater freedom of prosthetic design and the fabrication of more complex shapes [10], so it is the possibility to reconstruct defects in musculoskeletal oncology with personalized custom-made prostheses [11] . This technology can not only increase the accuracy of the reconstruction, but also reduce the rate of post-operative complications and potentially improving stability [12].…”
Section: Introductionmentioning
confidence: 99%